Fusarium oxysporum & Fusarium solani: Identification, Characterization, and Differentiation the Fungal Phenolic Profiles by HPLC and the Fungal Lipid Profiles by GC-MS - Nashwa M. Shalapy; Wenyi Kang (Journal of Food Quality)
Fusarium is a famous genus including a numerous species of endophytic fungi as it is known as a productive source of secondary metabolites which had various bioactivities. Fungal secondary metabolites are defined as chemical compounds produced by fungus and not essential for it. The common secondary metabolites of Fusarium sp. (e.g., phenols, flavonoids, alkaloids, saponins, and terpenes) had a wide range of biological properties comprising antioxidant, antidiabetic, antibacterial, antifungal, and cytotoxic activities. In this way, the present study was performed to evaluate the phenolic compounds and flavonoids of Fusarium oxysporum and Fusarium solani qualitatively and quantitatively via high-performance liquid chromatography (HPLC). Moreover, lipid criteria of Fusarium oxysporum and Fusarium solani extracts had been displayed by gas chromatography-mass spectrometry (GC-MS) and their fatty acids had been identified to define the prolific species of the most biological and valuable fatty acids. In discrimination between phenols and flavonoids of Fusarium oxysporum and Fusarium solani as natural biological constituents analyzed by HPLC, the methanolic extracts of Fusarium species revealed that phenols level was elevated in F. oxysporum than its level in F. solani as well flavonoids level was advanced in F. oxysporum compared to F. solani. Furthermore, the HPLC chromatograph showed significant detection for some phenols in F. oxysporum extract were disappeared in F. solani extract and also some flavonoids were detected in F. oxysporum extract were vanished in F. solani extract. On the other side, the quantitative lipid analysis of Fusarium species chloroform extracts showed significant elevation in F. oxysporum lipid amount compared to F. solani, as the qualitative lipid analysis by GC-MS indicated that the concentration of saturated fatty acids was receded in F. oxysporum (29.18%) than its concentration in F. solani (40.11%) and the ratio of oxidation was 3.73% in F. oxysoporum while in F. solani was 4.23%. These displayed data illustrated conclusively that Fusarium oxysporum had a wide medicinal effectiveness as antioxidant, anticancer, anti-inflammation, and cardioprotective action due to its plentiful content from valuable phenols, flavonoids, and fatty acids in comparison with F. solani, as it may be elected as an alternative natural drug for some pharmaceutical applications.